The East German leadership and the division of Germany patriotism and propaganda 1945-1953 - Spilker, Dirk, 1966- (Oxford historical monographs., 2006)
This is a study of the division of Germany after the Second World War and it draws on unpublished documents revealing the political realities of the situation in post-war Germany. It also reassesses the motivations and actions of the Western Allies and the Soviet bloc, as they manoeuvred to achieve their ends.